2008
DOI: 10.2164/jandrol.107.002717
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varicocele Repair on Experimental Varicocele‐Induced Testicular Germ Cell Apoptosis

Abstract: The purpose of this study was to evaluate the variance of apoptosis in rats in which experimental varicocele was induced and then treated by varicocelectomy. Forty adult male Wistar albino rats were used in this experimental study. Experimental varicocele was created in 30 rats. A total of 5 rats underwent a sham operation, and the remaining 5 rats were the control group. A total of 5 rats from the varicocele group were sacrificed on the 14th postoperative day, and 5 more were sacrificed on the 28th postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Small changes in ␥ -H2AX might explain why ␥ -H2AX in spermatogonia is not a marker for DNA damage but for DSB repair, since spermatogonial populations remain as a part of the stem cell, or undergo apoptosis, or continue to differentiate into mature spermatozoa [26] . These results raise the possibility that ␥ -H2AX immunopositive spermatogonia may play important roles in the functional restoration of testes if appropriate varicocelectomy is carried out as previously reported [22] .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Small changes in ␥ -H2AX might explain why ␥ -H2AX in spermatogonia is not a marker for DNA damage but for DSB repair, since spermatogonial populations remain as a part of the stem cell, or undergo apoptosis, or continue to differentiate into mature spermatozoa [26] . These results raise the possibility that ␥ -H2AX immunopositive spermatogonia may play important roles in the functional restoration of testes if appropriate varicocelectomy is carried out as previously reported [22] .…”
Section: Discussionsupporting
confidence: 79%
“…The incidence of apoptosis is increased in the varicocele under the terminal deoxynucleotidyl transferase-mediated dTUP nick-end labeling (TUNEL) assay [12,[22][23][24] and it can be corrected by surgical treatment [22] . Although there is no direct connection between varicocele and apoptosis, p53-mediated apoptosis is associated with the activation of caspases [10,11] .…”
Section: Discussionmentioning
confidence: 99%
“…To better define the multiple actions of PDRN in the testis, we also characterized the apoptosis machinery in our experimental model. Increased germ cell apoptosis has been found in the ejaculate of men with varicocele (20), and creation of varicocele in rats causes a marked activation of apoptosis (21). Our data allow us to hypothesize that the curative effects of PDRN are likely related to its ability either to induce VEGF (22,23), which causes an augmented oxygen supply, or to balance the apoptosis machinery, as evidenced by the reduction of proapoptotic Bax and increased levels of antiapoptotic protein Bcl-2.…”
mentioning
confidence: 53%
“…Fazlioglu et al (29) showed that after creation of unilateral varicocele, the apoptotic process was increased in both testes and that it decreased markedly after varicocelectomy. Moustafa et al (30) reported that apoptosis was significantly correlated with ROS within infertile patients in the whole ejaculate and in the mature and immature spermatozoa.…”
Section: Discussionmentioning
confidence: 99%